ANALISIS DAMPAK ZAKAT, INFAQ DAN SHODAQOH TERHADAP PENGENTASAN KEMISKINAN DI KABUPATEN LABUHANBATU SELATAN (Studi Kasus Masjid Darul Aman Martapotan Kelurahan Langga Payung) - Rahmat Kurniawan (STIE Trisna Negara OKU Timur, 2022)
Organized and systematic management of zakat, infaq and shodaqoh has a positive impact on poverty alleviation in South Labuhanbatu Regency. The problem in this study is how the impact of zakat, infaq and shodaqoh on poverty alleviation in South Labuhanbatu Regency and to determine the mechanism of zakat, infaq and Shodaqoh management in South Labuhanbatu Regency. This research is a qualitative research with a descriptive approach. The research area was carried out in South Labuhanbatu Regency, precisely at the Darul Aman Martapotan Mosque, Langga Payung Village. Data collection techniques using are observation, interviews and documentation. From the results of the study it can be concluded that the zakat, infaq, and shodaqoh funds given have a positive impact on economic growth in South Labuhanbatu Regency, so that it can reduce unemployment and reduce poverty. and the management of the Amil Zakat Agency with the method of collecting Zakat funds through the pick-up method with a friendly approach, and for infaq and shodaqoh funds by making Charity boxes in the mosque. For the distribution of zakat, infaq, and shodaqoh funds, it is given for consumptive and productive purposes on the condition that the mosque is prosperous by praying in congregation every time. Keywords: Zakat, Infaq, Shodaqoh, and Poverty